Real estate’s knowledge and device‐based decision support system - Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras; Banaitis, Audrius (International Journal of Strategic Property Management, 2010)
The authors of this paper participated in the European Union’s Sixth Framework Programme project Intelligent Cities (INTELCITIES, 2005). One of INTELCITIES’s goals (on the Lithuanian side) was to develop a Real Estate’s Knowledge and Device‐based Decision Support System (KDDSS‐RE). Major KDDSS ‐RE functions include creating and maintaining customer’s personalized real estate objectives, preferences, and evaluation criteria; participation of various stakeholders (buyers, sellers, brokers, etc.) in joint determination of criteria (criteria system, values and weights) defining real estate; market signalling, provide device‐based data about indoor microclimates and allergens causing allergy in buildings; searching for real estate alternatives, finding alternatives and making an initial negotiation table, completing a multiple criteria analysis of alternatives, making electronic negotiations based on real calculations, determining the most rational real estate purchase variant, and completing an analysis of loan alternatives offered by certain banks. The authors of the present research have suggested the idea to integrate knowledge‐based, devices‐based and decision support systems. In order to demonstrate the integration decision support, knowledge and devices systems in the real estate sector a Real Estate’s Knowledge and Devices‐based Decision Support System have been considered in the paper as an example. First Published Online: 09 Jun 2011